PENYELESAIAN SENGKETA TANAH TERKAIT EIGENDOM VERPONDING YANG DIKUASAI PIHAK LAIN - Amelia Akef Abdat, (2021)
Since the enactment of the UUPA on September 24th 1960, eigendom verponding land rights must be converted into property rights for Indonesian citizens and land use rights for foreign citizens within 20 years since the UUPA was enacted 24 September 1980. However, in practice after 20 years The UUPA was promulgated there are still many owners of eigendom verponding land rights who have not converted them to property rights or building use rights so that land tenure disputes arise by other parties but the owners still hold the rights to the eigendom verponding land. So that the purpose of this research is to find out and understand the power of proof of eigendom verponding against land disputes controlled by other parties and to know and understand how to return the rights to eigendom verponding land controlled by other parties. The research method used in this study is a normative juridical method and it can be concluded that: Eigendom verponding's evidentiary power is based on Government Regulation Number 24 of 1997 concerning Land Registration, land rights derived from European legal rights including eigendom verponding land rights can be registered with strong evidence to be converted into property rights even though the conversion deadline has passed. The way to return eigendom verponding which is controlled by another party is by suing and proving that there is an error in the certificate issuance process which causes an overlap and after being sued the owner of the eigendom verponding land rights must convert it into property rights. His suggestion to owners of land rights eigendom verponding must convert by including strong evidence. As well as to the BPN to be more careful in issuing certificates so that there is no overlap in ownership of land rights. Keywords: Eigendom verponding, land rights, other parties.